THE MEDIATION OF LOCAL CULTURES WITH GLOBAL PERSPECTIVE IN FOREIGN LANGUAGE LEARNING - Syaefudin, Mohamad (Universitas Negeri Semarang, 2014)
Foreign language learning with local culture contents began from the importance of the representation of the roots of the nation in foreign language. Foreign language learning strategies which mediate local cultures and cultural values existed in a foreign language generate a global perspective on foreign cultures, not only on the articulation of local messages to foreign languages, but also it compares how the local values are relevant to the values of other nations. Eventually, learners realize that by understanding themselves, they will be able to appreciate the wisdom of other nations. French culture which was compared to Javanese cultures in this article proved the statement above.